Influences of greenhouse-integrated semi-transparent photovoltaics on microclimate and lettuce growth - Hassanien, Reda Hassanien Emam; Ming, Li (International Journal of Agricultural and Biological Engineering, 2017)
Shading in greenhouses is a simple and cheap method usually used to reduce the intensity of solar radiation and air temperature. Moreover, combining Photovoltaic (PV) panels and crops on the same cropland could alleviate the increasing competition for the agricultural land between food and energy production. In addition, the integration of PV with greenhouses could reduce, or partially replace the energy consumption for greenhouse crop production. Therefore, the aim of this study was to investigate the shading effect of semi-transparent mono-crystalline silicon double glazing photovoltaic panels (STPV), mounted on top of an agricultural greenhouse, which occupied 20% of the roof area, on the microclimate conditions and the growth of lettuce plants inside a greenhouse. Results showed that the combination of STPV and polyethylene cover decreased the solar radiation by 35% to 40% compared to the use of polyethylene cover only for clear days which was in the acceptable range of photosynthetically active radiation for lettuce plants. Moreover, STPV shading decreases the air temperature by 1°C-3°C and had no effect in the relative humidity under natural ventilation. Furthermore, there were no significant differences (p0.05) in the growth of lettuce plants between the shaded greenhouse by the STPV and the unshaded. Shading insignificantly increased the fresh weight, leaf area and the chlorophyll contents (p0.05). In conclusion, the integration of STPV modules can decrease the solar irradiation and the internal air temperatures as well as generate electric energy for environmental control systems without significant influence on the growth of lettuce plants. Meanwhile, it can decrease the water consumption by decreasing the evapotranspiration rate.Keywords: semi-transparent photovoltaics, greenhouse, shading, lettuce growth, microclimate, energy consumptionDOI: 10.25165/j.ijabe.20171006.3407Citation: Hassanien R H E, Li M. Influences of greenhouse-integrated semi-transparent photovoltaics on microclimate and lettuce growth. Int J Agric & Biol Eng, 2017; 10(6): 11–22.